The power of gender & the gender of power : explorations in early Indian history - Roy, Kumkum (New Delhi : Oxford University Press, 2010)
On feminism in early India and its depiction in various ancient and medieval Indic literature; articles.
pt. 1. Towards histories of gender relations -- pt. 2. Interrogating textual traditions.
Includes bibliographical references and index.
Keywords: Feminism -- India -- History; Women -- India -- History; Indic literature -- To 1500 -- History and criticism